Long-term outcomes of functional surgery for attic cholesteatoma - Atalay Çetinkaya, Erdem; Çukurova, İbrahim and Olgun, Levent and Kabakçı, Raci (ENT Updates, 2016)
Objective: To evaluate the long-term findings obtained using microscopic approaches to attic cholesteatoma and with respect to the reconstruction materials used in ossiculoplasty. Methods: The results of these procedures were evaluated in 30 of the patients who subsequently returned for follow-up. One of the surgical techniques among atticotomy + tympanoplasty, intact canal wall tympanoplasty (ICWT) and canal wall-down tympanomastoidectomy (CWDT) was performed. The responses to procedures based on postoperative complaints, otoscopy and audiometry results were evaluated and compared with those pre-treatment. Results: A comparison of the preoperative and postoperative air-bone differences in 26 (85%) patients showed a hearing gain of 5–35 dB. The largest gain was achieved with ICWT type II surgery. Evaluation of the tympanic membrane by microscopic otoscopy showed various degrees of retraction in 30% of the patients in the open group and approximately 20% of those in the closed group. After a six-year long-term followup, 55% of the patients in the open group and 45% of those in the closed group had normal findings. Conclusion: An adequate exposure allowing full removal of an attic cholesteatoma may require an open technique. Compared to closed techniques, this also allows hearing preservation and ossicular reconstruction. Good results in the reconstruction of the ossicles can be achieved using recently developed biomaterials, assuming that the stapes and manubrium mallei are in good condition.